Endoscopic interventional therapies for tracheoesophageal fistulas in children: A systematic review - Ling, Yaozheng; Sun, Bingyue; Li, Junhui; Ma, Li; Li, Deli; Yin, Guo; Meng, Fanzheng; Gao, Man (Frontiers in Pediatrics, 2023)
Introduction: Tracheoesophageal fistula in children is a relatively rare congenital anomaly. The endoscopic intervention remains an interesting alternative to surgery due to less invasive characteristics, there are numerous endoscopic interventional techniques for TEF in children. The purpose of this review is to summarize and assess the characteristics and overall success rate of published endoscopic interventional techniques in order to provide clinical guidance for pediatricians. Methods: An electronic literature search was performed using the keywords “tracheoesophageal fistula”, “endoscopic” and “children” in the four major medical databases (Ovid, Embase, PubMed and Web of science) from inception to September 2022. All English language articles describing the endoscopic interventional therapies of TEF in children were reviewed. Two independent researchers screened eligible articles at title and abstract level. Relevant data was extracted and analyzed. A synthesis of the relevant data is presented in descriptive form due to theheterogeneity of the included articles. Results: A total of 46 studies describing 170 TEF patients in an age range of 0.3-175 months were enrolled. 119 out of 170 cases were successfully blocked via endoscopic techniques with an overall success rate of 70.0%, while 48 cases failed to close by endoscopic interventions and converted to open surgery. The comparatively assessment of different endoscopic interventional techniques for TEF detected that endotracheal stenting was performed in six cases and one case were successfully blocked (16.7%), de-epithelialization alone was performed in 65 cases and the fistula got healed in 47 cases (72.3%), chemical sealant injection was performed in 33 cases and got success in 21 cases (63.6%), de-epithelialization in combination with chemical sealant injection was performed in 62 cases and got relatively highest success rate of 77.4% (48 cases). Other treatment methods were performed in four cases and successfully treated in two cases (50.0%). Conclusion: The endoscopic intervention is currently a preferred treatment modality for children with TEF. Among the interventional techniques, De-epithelialization in combination with chemical sealant has a higher success rate than other techniques, However, due to limited cases for many kinds of techniques, the ideal endoscopic interventional technique is yet to be determined and more applications are often necessary